The Impact of Social Change on the Childfree in the view of Sadd al-Żarīʻah - Nimah, Rodhotun; Tahir, Achmad (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Economic and ideological structural changes resulted in demographic shifts. Current economic constraints, including the demand for higher levels of education and concerns about future jobs, are driving a demographic shift towards delaying having children. In Indonesia, the public has been excited about the child-free phenomenon. Childfree is a decision made by humans, both male and female, not to have children in a life that goes on, be they biological children or adopted children. Eastern culture, social construction, and stigma have not been able to accept the concept of childfree. This research library uses an Islamic law approach (Sadd al-Żarīʻah). The type of research used is qualitative research. Using a normative approach (Sadd al-Żarīʻah) shows that having offspring is a recommendation in Islam and not necessary. Childfree is not an act that is prohibited because every couple has the right to regulate their domestic life, including having children. However, we also do not need to worry about our survival if we have many children because Allah has guaranteed the lives of his servants.